A construção da atuação no cinema: um estudo a partir das experiências dos atores Irandhir Santos e Hermila Guedes - Gouveia, Maria Alice Lucena de (2016)
This research derives from my need of understanding the actor’s preparation process in the Pernambuco cinema, by means of its deconstruction. Therefore, my object of study will be the immersion work of actor Irandhir Santos, who played the main character of the following movies: Rat Fever (2011), by Cláudio Assis; Tattoo (2013) by Hilton Lacerda; Neighboring Sounds (2013) by Kléber Mendonça and História da Eternidade (2014), by Camilo Cavalcante. In the same manner, I will study the works of actress Hermila Guedes: Once Upon A Time Veronica, (2014) by Marcelo Gomes and Love for Sale, (2006), by Karim Aïnouz. This corpus focuses on the cinema produced recently in the state of Pernambuco, Brazil, that were conceived through a collaborative process - in which the actor finds itself being in a highlighted position, while formatting the final structure of the movie’s narrative. As a methodological approach, I propose the use of “Crítica de Processos”, elaborated by researcher Cecília de Almeida Sales (2006). It seeks to understand the process of artistic creation through its testimonies, its footprints and the active observation of the elaboration of a movie